Ornamental Art of Kalasan Temple in The Perspective of Art Philosophy - Niken Wirasanti (Mudra Jurnal Seni Budaya, 2023)
The beauty of Kalasan Temple faÃ§ade can be seen from its variety of decorations known as the pearls of Central Java art in the 8th century AD. The artwork manifests in the aesthetics and artistic value of Kala-Makara, leaf tendrils (purnakalasa), paper paste, apsara-apsari figures. The purpose of this writing is to gain knowledge and insight about the decorative artistic expressions carved on the temples. The method used is qualitative research observing its form, content and meaning. The analysis uses contextual analysis, which is to look at the relationship between ornaments and their context by basing on the motion of lines, the shape of art objects, and rhythmic compositions. The discussion will use aesthetic theory, artistic value and symbol theory to be able to explain the form of beauty in the decorative art of Kalasan Temple. The result shows that the selection of ornamental art ornaments is combined with the right proportions, symmetry in the arrangement and precise processing to produce artistic expression in achieving transcendent ideas.